Farmer services: Direct data on demand - Gantt, Whitney; Cantor, Eric (Technical Centre for Agricultural and Rural Cooperation, 2010)
A network of community knowledge workers (CKWs) in Uganda uses a suite of mobile applications to give farmers a broad range of information. The CKWs can provide farming advice, market data, pest- and disease-control training, plus weather forecasts.